2016
DOI: 10.5858/arpa.2015-0081-oa
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Utility of PAX8 Immunohistochemical Stain in Diagnosing Endocervical Glandular Lesions

Abstract: Context.-PAX8, a member of the paired-box family of genes, is expressed in many tumors of Müllerian origin. However, it is unclear whether PAX8 is a useful marker in diagnosing endocervical glandular lesions because of limited data.Objective.-To study the expression of PAX8 in endocervical glandular lesions.Design.-We first studied a cohort of 29 cervical cone biopsies, followed by a second cohort of 17 cases of endocervical adenocarcinoma and 20 cases of uterine endometrioid adenocarcinoma.Results.-In the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 15 publications
(25 reference statements)
3
16
0
Order By: Relevance
“…The expression of p16INK4A in WD and MD was diffusely positive. This result was the same with the finding in other study that p16INK4A was expressed in diffusely or strongly expression in cervical intraepithelial neoplasia I, II, III, squamous cell carcinoma, endocervical glandular dysplasia, adenocarcinoma in situ, and invasive adenocarcinoma (Tringler B et al 2004); as well as in endocervical carcinoma (Liang et al 2016). The finding in this study was in accordance with the results of other studies.…”
Section: Discussionsupporting
confidence: 93%
“…The expression of p16INK4A in WD and MD was diffusely positive. This result was the same with the finding in other study that p16INK4A was expressed in diffusely or strongly expression in cervical intraepithelial neoplasia I, II, III, squamous cell carcinoma, endocervical glandular dysplasia, adenocarcinoma in situ, and invasive adenocarcinoma (Tringler B et al 2004); as well as in endocervical carcinoma (Liang et al 2016). The finding in this study was in accordance with the results of other studies.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, a high frequency of PAX-8 expression was noted among females diagnosed with endometrium cancer compared to SCC, this finding is in contrary with a previous report where PAX-8 was expressed among only 3% of the studied samples [37]. Also, the result was strongly in accordance with other studies [13,38,39]. Besides that, the lack of PAX-8 expression among those who were diagnosed with well differentiated SCC and metastatic adenocarcinoma could play a significant role in either gynecologic cancer differentiation or in detection of endometrium adenocarcinoma progression to metastatic adenocarcinoma [40,41].…”
Section: Discussionsupporting
confidence: 74%
“…23,24 The tumor cells are negative for PR (Figure 2, D) and vimentin, and negative or only weakly positive for ER. 23,24 The Ki-67 labeling index is usually higher than 25%, with average 52% staining. 13 In a study of phosphatase and tensin homolog (PTEN) expression in ADCs, 88% of cases showed at least focal positivity.…”
Section: Immunohistochemical Markersmentioning
confidence: 98%
“…Endocervical ADC shows diffuse and strong cytoplasmic and nuclear positivity for p16 ( Figure 2, C), 10,23-25 cytoplasmic or membranous carcinoembryonic antigen (CEA) positivity, 23,24 and strong to weak nuclear PAX8 positivity. 23,24 The tumor cells are negative for PR (Figure 2, D) and vimentin, and negative or only weakly positive for ER. 23,24 The Ki-67 labeling index is usually higher than 25%, with average 52% staining.…”
Section: Immunohistochemical Markersmentioning
confidence: 99%